Konseptualisasi dan desain perencanaan pendidikan berbasis teknologi digital di sekolah menengah atas - Mustika, Lutfia Richa Ayu; Lisnanto, Suko; Warsiyatun, Warsiyatun; Widyarto, Alvin; Nyoman, Ngurah Ayu (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2025)
The digital era has significantly transformed the way people live, work, and learn. In the field of education, technological advancements such as artificial intelligence (AI) and digital platforms offer immense opportunities to enhance teaching and learning processes. However, successful integration of these technologies requires careful planning and strategic implementation. This study aims to analyze digital technology is planned, organized, implemented, and evaluated in the learning process at SMA Negeri 1 Tuntang, a school recognized for its active use of digital platforms in teaching. Employing a qualitative descriptive method, data were collected through participatory observation, semi-structured interviews, and documentation, involving 10 teachers and 30 students as purposive sampling. The findings reveal that the school developed a structured strategy for integrating digital technology, including the use of Google Classroom, educational games, and interactive videos, supported by stable internet infrastructure and ongoing teacher training. The implementation process emphasized accessibility, user-friendliness, and low-cost solutions to accommodate students from rural areas. The SWOT analysis revealed that digital tools play a significant role in promoting student engagement, strengthening digital competencies, and enabling personalized learning pathways. This study underscores the importance of comprehensive planning and institutional support in realizing the full potential of educational digitalization.